Acute Postpartum Pulmonary edema: A Case Report - Akhtar, Ahreen; Dorji, Namkha; Parveen, Tabassum; Dorjey, Yeshey; Begum, Firoza; Hayee, Samira; Karim, Sabina (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
A 30 year old, G2P1, pregnancy complicated with moderate anaemia, preeclampsia andgestational diabetes mellitus was admitted at 37+ week pregnancy with less fetal movementand premature rupture of membrane. A healthy baby was delivered by caesarean sectionwith uneventful perioperative period. On 4th post operative day, she developed severe acutepulmonary edema where intubation was done instantly and ventilated in the intensive careunit. Patient recovered and extubation done on 6th postoperative day. A healthy mother anda healthy baby were discharged on 10th postoperative day. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 157-159